Exosomes Derived from HIV-1 Infected DCs Mediate Viral trans-Infection via Fibronectin and Galectin-3. Issue 1 (December 2017) - Kulkarni, Rutuja; Prasad, Anil
Abstract Exosomes are membrane enclosed nano-sized vesicles actively released into the extracellular milieu that can harbor genomic, proteomic and lipid cargos. Functionally, they are shown to regulate cell-cell communication and transmission of pathogens. Though studies have implicated a role for exosomes in HIV-1 pathogenesis, their mechanisms are not well defined. Here, we characterized exosomes derived from uninfected or HIV-1 infected T-cells and DCs. We demonstrate substantial differences in morphological, molecular and biogenesis machinery between exosomes derived from these two immune cell types. In addition, exosomes derived from HIV-1 infected DCs were 4 fold more infective than either cell free HIV-1 or exosomes derived from T-cells. Molecular analysis of exosomes detected the presence of fibronectin and galectin-3 in those derived from DCs, whereas T-cell exosomes lacked these molecules. Addition of anti-fibronectin antibody and β-lactose, a galectin-3 antagonist, significantly blocked DC exosome-mediated HIV-1 infection of T-cells. We also observed increased gene expression of the pro-inflammatory cytokines IFN-γ, TNF-α, IL-1β and RANTES and activation of p38/Stat pathways in T-cells exposed to exosomes derived from HIV-1 infected DCs. Our study provides insight into the role of exosomes in HIV pathogenesis and suggests they can be a target in development of novel therapeutic strategies against viral infection.